Recent Trends in Live Feeds for Marine Larviculture: A Mini Review - Pan, Yen-Ju; Dahms, Hans-Uwe; Hwang, Jiang-Shiou; Souissi, Sami (Frontiers in Marine Science, 2022)
In marine larviculture, farmed larvae mainly rely on the alimentation of a group of small-sized phytoplankton and zooplankton referred to as live feed. Under the diversifying demands of human consumption and ornamental aquarium industry, new species of live feed and their innovative production methods are essential focuses for sustainable larviculture of many emerging fish and invertebrate species. The selection of proper live feed for larval feeding is based on several parameters, such as size, morphology, nutritional value, stock density and growth rate. This review aims to highlight the biological characteristics, production approach, common larviculture applications as well as recent innovations in the aquaculture technology of live feed organisms (microalgae, ciliated protists, rotifer, Artemia, copepod and others).